2008
DOI: 10.3329/jsr.v1i1.1053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molybdate, Nitrite and Zinc Ions on the Corrosion Inhibition of Mild Steel in Aqueous Chloride Media Containing Cupric Ions

Abstract: An investigation has been conducted on the corrosion inhibition of mild steel by molybdate, nitrite and zinc ions in aqueous chloride media containing cupric ions. Molybdate inhibits mild steel corrosion in near neutral and alkaline (pH 6 and above) chloride media and accelerates corrosion in acidic media (below pH 6) both in the presence and absence of cupric ions. Nitrite inhibits mild steel corrosion in chloride media at pH 4.5 and above, but accelerates corrosion below pH 4.5 both in the presence and absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Cl -and SO42 -ions are specifically adsorbed onto the metal and create an excess of negative charge on its surface. 17,18 This favours the adsorption of protonated MDMAE on the surface through electrostatic attraction and hence reduces the dissolution of Fe to Fe…”
Section: Mechanism Of Inhibitionmentioning
confidence: 99%
“…Cl -and SO42 -ions are specifically adsorbed onto the metal and create an excess of negative charge on its surface. 17,18 This favours the adsorption of protonated MDMAE on the surface through electrostatic attraction and hence reduces the dissolution of Fe to Fe…”
Section: Mechanism Of Inhibitionmentioning
confidence: 99%
“…Molybdates, tungstates and metavenadates so on are now being increasingly used as the green inorganic corrosion inhibitors especially because of their lower toxicity (Ali et al, 2009;Celeste and Idalina, 2004;Li et al, 2011;Sribharathy and Rajendran, 2012;Zhao and Zuo, 2002). It was reported that the synergistic effect of anodic inhibitors (i.e., vanadates, molybdates, tungstates, phosphates, borates) and cathodic inhibitors (i.e., Ce, Y, La, Eu, Gd and Nd) those are proved to be more suitable to substitute the toxic inhibitor of chromates (Tayler and Chambers, 2009).…”
Section: Research Articlementioning
confidence: 99%
“…There is great interest in replacing chromates with effective and non-hazardous alternatives green corrosion inhibitors. Nitrites, molybdate, tungstate are now being increasingly used as eco-friendly green inorganic corrosion inhibitors, because of their low order of toxicity (Subedi et al, 2014;Eghbali et al, 2011;Zhao and Zuo, 2002;Celeste and Vieira, 2004;Saji and Thomas, 2007;Ali et al, 2009;Refaey et al, 2000;Pryor and Cohen, 1953;Lizlovs, 1976;Farr and Saremi, 1982;Mustafa and Dulal, 1997).…”
Section: Introductionmentioning
confidence: 99%